Psikhologicheskie aspekty postroeniya sorevnovatel'nogo povedeniya v sporte - Maltchikov, A. V. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The problem of an athlete's behavior in situation of competition is in the center of the article. The author shifts an accent from athlete's pre-competitive psychological training toward real competitive behavior. Notions of psychological strategy and tactics, competitive plan and intention had been discussed in details. Besides that, the author had substantiated five main characteristics of on athlete's competitive behavior (Pentabasis) scientifically and named them as "independent variables". According to the author's opinion, all of these characteristics are locked on an athlete's personality and stay in direct dependence of it.